LEO satellite communication and navigation symbiosis positioning management based on signal of opportunity - Jie SHEN; Hui LIU; Jianbing RAO; Quan HE; Liyan BEN; Zhizhong WANG; Ying XIONG (Dianxin kexue)
Communication and navigation symbiosis refers to the coexistence of these signals in the satellite ecological environment.For single-function low-orbit satellite constellations for positioning or communication, it is difficult to quickly perform positioning management when positioning or communication signals are unavailable.The extended Kalman filter (EKF) algorithm was proposed to solve the location of the opportunity signals of LEO communication navigation symbiosis constellations, breaking through the dependence of location management on a single navigation system.Firstly, the basic principle of Kalman filter was introduced, and a Kalman filter location management algorithm based on opportunity signal combining with the positioning management algorithm of LEO satellite constellation was proposed.Secondly, the advantages of this algorithm were analyzed, including improving positioning accuracy, improving positioning efficiency, improving positioning stability, etc.Finally, experiments were carried out to verify the effectiveness of the algorithm.The results show that the algorithm can effectively improve the positioning accuracy, efficiency and stability, and provides an effective solution for LEO communication navigation symbiosis constellation location management.